Study on flight and collision process of molten blast furnace slag - WANG Kai; YI Chui-jie; HU Feng-chao; ZHAN Sheng (Fenmo yejin jishu)
The mathematical model was established for the flight process of the molten blast furnace slag after the centrifugal graining, and the model was discretely solved by the Runge-Kutta method. The results show that, the flight distance of the slag droplets along the x direction is proportional to the diameter and the initial velocity of droplets. Due to the air flow resistance and gravity, the velocity of droplets decreases with time, and then increases slightly. Critical impact velocity of the droplets was proposed by analyzing the excess rebound energy of the slag droplets after collision with wall. The results indicate that, the critical impact velocity is an interval, and the larger the droplets, the lower the bounds. The experiments were performed with the initial droplet velocities of 10, 12, and 14 m·s‒1. The results indicate that, the actual falling distance of the slag droplets is greater than the theoretical values, because the initial velocity of the slag droplets is less than the linear velocity of the granulation plate. Meanwhile, the impact velocity of the slag droplets is between the upper and lower bound, thus no adhesion occurs.